Heating systems through the lens of the boiler: Detailed case studies to inform current and future heating system design. (May 2020) - Bennett, George
Boilers in hydronic heating systems are the norm in the UK. Through case study analysis, covering four houses with gas central heating systems for over one year and utilising novel monitoring of the on-board diagnostic data of the boilers, performance issues were identified in this mature technology. ON/OFF cycling behaviour and oversizing were prevalent with boilers consistently unable to modulate low enough to match the building space heating demand. Cycling behaviour resulted, known to be detrimental to efficiency, with the majority of boiler operations lasting less than 10 min. Targeted case study analysis of incumbent technologies, such as boilers, utilising the latest in data collection techniques and connected appliances provides a cost effective insight to broader issues. Implications for domestic energy demand range from incremental improvements in boiler system efficiency by addressing cycling to the updating of building energy assessment models (e.g. Standard Assessment Procedure) to reflect and reward the benefits of good installation practices. An improved understanding of boiler operation may support improved product design and installation practices and are beneficial to the next generation of domestic heat, such as heat pumps. By undertaking continued in situ analysis of the incumbent technology, a more thorough foundation for the future can be ascertained. Practical application : Fundamental issues of oversizing and detrimental cycling behaviour are persisting in the industry. Practical steps can be taken immediately to avoid oversizing of boilers. Building an awareness of performance penalties associated with poorly planned heating installations will have added benefit for more dynamically sensitive technologies in the future, such as heat pumps.